2015
DOI: 10.1111/jsm.12944
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Prospective Double-Blind Comparison Trial of Clomiphene Citrate and Anastrozole in Raising Testosterone in Hypogonadal Infertile Men

Abstract: Aim Clomiphene citrate (CC) and anastrozole (AZ) have been used off label to increase testosterone (T) in hypogonadal infertile men (HIM). Both medications have been shown to increase T with different effects on estradiol (E2) and T-to-E2 ratios. There are no reported randomized trials comparing CC and AZ to improve T levels in HIM. We aimed to establish equivalence of CC vs. AZ with respect to improvement in T levels in HIM. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
152
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(157 citation statements)
references
References 51 publications
2
152
0
3
Order By: Relevance
“…Hormonal changes may include increased leptin, oestrogen and insulin levels and decreased testosterone levels (Du Plessis, Cabler, McAlister, Sabanegh, & Agarwal, ). Continuity of spermatogenesis and sperm quality depend on high levels of intratesticular testosterone (Helo et al, ). High oestrogen levels had a direct detrimental effect on spermatogenesis in an animal model study (Hammoud, Gibson, Peterson, Hamilton, & Carrell, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal changes may include increased leptin, oestrogen and insulin levels and decreased testosterone levels (Du Plessis, Cabler, McAlister, Sabanegh, & Agarwal, ). Continuity of spermatogenesis and sperm quality depend on high levels of intratesticular testosterone (Helo et al, ). High oestrogen levels had a direct detrimental effect on spermatogenesis in an animal model study (Hammoud, Gibson, Peterson, Hamilton, & Carrell, ).…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized, double blinded study the researchers demonstrated that clomiphene resulted in significantly higher testosterone levels than anastrozole (28). Increase in testosterone was 130% in the clomiphene group vs. 69% in the anastrozole group ( Figure 1 ).…”
Section: Aromatase Inhibitors (Ai)mentioning
confidence: 99%
“…AZ is an aromatase inhibitor that decreases the conversion of testosterone to oestradiol. As a result of this mechanism, AZ produces a significantly higher testosterone:oestradiol ratio than CC . Oligozoospermic men with hypoandrogenism and a low testosterone:oestradiol ratio had significantly improved endocrine and semen variables after treatment with AZ .…”
Section: Introductionmentioning
confidence: 99%